OPTIMIZING JOB SATISFACTION THROUGH WORK-LIFE BALANCE AND WORKLOAD APPROACHES AMONG EMPLOYEES OF BPJS KESEHATAN PALU BRANCH OFFICE - Dedi Defretes Waang; Harnida Wahyuni Adda; Yoberth Kornelius; Moh. Ali Murad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to analyze the influence of work-life balance and workload on employee job satisfaction. The study was conducted at BPJS Kesehatan Palu Branch, utilizing a quantitative approach. Data was collected from 30 employees through observations and questionnaires. The sampling method employed was non-probability sampling with a saturated sampling approach. The data was then analyzed using SPSS version 30.0.The results indicate that, based on multiple linear regression analysis, there is a negative influence of respondents' perceptions regarding work-life balance on job satisfaction, while workload has a positive and significant effect on job satisfaction. Hypothesis testing, conducted both simultaneously and individually using F-tests and t-tests, showed that work-life balance (X1) and workload (X2) significantly affect job satisfaction (Y), with p-values of (0.001 and < 0.001) < 0.05, indicating a significant collective influence.